Plasma reactor for material synthesis and waste recycling; Energy Fluxes and Radiation Effects (EFRE); International Conference on Modification of Materials with Particle Beams and Plasma Flows (16th CMM) - Bolatova Zh. S. Zhanar Sanatovna; Pak A. Ya. Aleksandr Yakovlevich; Gumovskaya A. A. Arina Andreevna; Povalyaev P. V. Pavel Vadimovich; Martynov R. S. Roman Sergeevich; Larionov K. B. Kirill Borisovich (2022, 2022)
Title screen